Perilaku Mengemudi Berisiko - Maria Chrisnatalia; Dian Kemala Putri; Stephanus Benedictus Bera Liwun (Humanitas (Jurnal Psikologi), 2023)
Several accidents while driving occur in early adulthood. This study aims to describe risky driving-behavior in early adulthood using four-wheeled vehicles and to determine risky driving-behavior in early adulthood which is influenced by aggressive driving and attitudes towards driving safety. The measurement tools used are risk driving scale, driving anger inventory and attitude scale towards driving safety. The method used in this study was quantitative, with a purposive sampling technique. The subjects obtained were 151 car drivers who had a driver's license for at least one year. The results of this study are that there are relations between aggressive driving and driving safety attitudes on one hand, and risky driving-behavior on the other.